Picturing the workers' Olympics and the Spartakiads - Strożek, Przemysław, 1983- author.
1 online resource.
Keywords: "This volume focuses on the modernist and avant-garde engagement with workers' sport events that were organised or were planned to be organised in the cities of Central Europe and the USSR in the period of 1920-1932: Frankfurt am Main - Vienna - Moscow - Prague - Budapest - Berlin. This volume is of great use to students and scholars of the history of sport, art history and cultural history in interwar Europe and the Soviet Union"--